Pemanfaataan Obat Tradisional Sebagai Pengobatan Alternatif Individu Di Indonesia - Theresiana, Yunita; Kamaluddin; Sriati; Lili Erina (Kodepena Indonesia, 2024)
Traditional medicine is the cultural heritage of the Indonesian nation that needs to be preserved and developed to support the nation's health development while improving the people's economy. Until now, traditional medicine is an alternative that is still widely used by the people of Indonesia. One of the traditional medicine used by most Indonesian people is herbal medicine. This study aims to analyze the influence of individual characteristic of drug user as an alternative medicine. Methods: This research is an analytic survey with cross sectional approach. Methods: The number of respondents is 400 samples.The sampling technique is done randomly based on the village clusters. Data collection is performed through interviews using questionnaires. Data analysis techniques use univariate and bivariate analysis using chi square test.Results: The results of bivariate analysis show that age, sex, education, occupation, ethnicity and variables utilization of traditional medicine are significant.Conclusion: Encouraging the achievement of acceleration of MDGs (Millennium Development Goals) through efforts to promote and preventif Traditional Health Services, especially through the utilization of traditional medicine that has been tested clinical and laboratory by experts in their field of individual user of traditional medicine as an alternative medicine is influenced by sex, education, occupation and ethnicity seem that those are individual characteristic are significant but age variable does not affect one's behavior because traditional medicine is easy to obtain and cheaper in terms of costs incurred.